Thresholds in macroinvertebrate biodiversity and stoichiometry across water-quality gradients in Central Plains (USA) streams - Evans-White, Michelle A.; Dodds, Walter K.; Huggins, Donald G.; Baker, Debra S. (My University, 2012)
N and P often limit primary and secondary production in ecosystems, but they also can cause eutrophication and negatively influence sensitive species above a certain level or threshold point. Aquatic biodiversity can have negative threshold relationships with water-quality variables at large scales, but the specific mechanism(s) driving these threshold relationships are not well established. We hypothesized that resource quality (i.e., C:P) might partly drive primary consumer (grazer and detritivore) richness thresholds by altering competitive interactions among species with differing resource demands, but might have less influence on predator richness. We estimated total N (TN), total P (TP), and turbidity thresholds for macroinvertebrate richness across trophic levels and feeding groups in Central Plains (USA) streams. We also determined if mean taxon body C:P of groups with diversity losses were negatively related to TP, a pattern that would suggest that eutrophic communities were dominated by a few species with high dietary P demands. Primary consumers were more sensitive to TN and TP (threshold mean  =  1.0 mg N/L and 0.06 mg P/L) than secondary consumers (threshold mean  =  0.09 mg P/L), a result supporting the resource quality hypothesis. Turbidity reduced richness regardless of feeding mode (threshold mean  =  4.7 NTU), a result suggesting that turbidity and nutrient thresholds were driven by different factors. The TP-richness threshold could be driven partially by changes in food quality because the mean body C:P of shredding and collector-gathering taxa declined as TP increased (threshold mean  =  0.07 and 0.75 mg P/L, respectively). Mean scraper C:P was not related to TP, a result indicating other factors might be responsible for the scraper richness threshold. Our results suggest that changes in resource quality could contribute to large-scale losses in biodiversity in nutrient-enriched lotic ecosystems. Within shredder and collector-gatherer macroinvertebrate feeding groups, P-rich food might allow faster growing taxa with high body P demands to out-compete slower growing taxa adapted to lower quality food resources. This pattern suggests that biotic integrity is directly linked to nutrients in streams and that toxicity, low dissolved O2, and increased turbidity might not be the only mechanisms leading to reductions in diversity as nutrient concentrations increase.
Keywords: Breakpoints; Nutrient criteria; Species richness; Bioassessment; Eutrophication; Water quality